Read and write offset estimation algorithm of hard disk drives caused by wind - Kleangsong, Theerayut; Thongnoo, Krerkchai; Jindapetch, Nattha (Asia-Pacific Journal of Science and Technology, 2017)
The aim of this research article was to study the read/write offset estimation algorithm to compensate slider displacement caused by wind inside a hard disk drive. The computer simulation model was used to simulate the slider displacement. The results of the displacement of the slider and read/write offset (RWO) obtained from the slider design were combined to the total read/write offset. Then, the total read write offset was used as the input to the estimation algorithm. The estimation algorithm was modified to achieve the acceptable error. It is found that, the suitable estimation algorithm is obtained by selecting the appropriate measuring positions, adjusting the number of the appropriate measuring points, and the use of spline-associated polynomial interpolation.